Caner-Liese, Robert (2018). El primer Romanticisme alemany: Friedrich Schlegel i Novalis - Sales Vilalta, Guillem (Enrahonar. An international journal of theoretical and practical reason, 2020)
Caner-Liese, Robert (2018) El primer Romanticisme alemany: Friedrich Schlegel i Novalis Barcelona: Edicions de la UB, 229 p. ISBN 978-84-9168-120-5